Community Benefit Spending Among North Carolina's Tax-Exempt Hospitals After Performing Community Health Needs Assessments. Issue 4 (July 2019) - Fos, Elmer B.; Thompson, Michael E.; Elnitsky, Christine A.; Platonova, Elena A.
Abstract : Context: As of March 23, 2012, the Internal Revenue Service (IRS) requires tax-exempt hospitals to conduct Community Health Needs Assessment (CHNA) every 3 years to incentivize hospitals to provide programs responsive to the health needs of their communities. Objective: To examine the distribution and variation in community benefit spending among North Carolina's tax-exempt hospitals 2 years after completing their first IRS-mandated CHNA. Design: Cross-sectional study using secondary analysis of published community benefit reports. Community benefit was categorized on the basis of North Carolina Hospital Association's community benefit reporting guidelines. Multiple regression analysis using generalized linear model was used to examine the variation in community benefit spending among study hospitals considering differences in hospital-level and community characteristics. Setting: Fifty-three private, nonprofit hospitals across North Carolina. Main Outcome Measure: Dollar expenditures as a percentage of operating expenses of the 2 categories of community benefit spending: patient care financial assistance and community health programs. Results: Study hospitals' aggregate community benefit spending was $2.6 billion, 85% of which was in the form of patient care financial assistance, with only 0.7% of total spending allocated to community-building activities such as affordable housing, economic development, and environmental improvements. On average, the study hospitals' community benefit spending was equivalent to 14.6% of operating expenses. Hospitals with 300 or more beds provided significantly higher investments in community health programs as a percentage of their operating expenses than hospitals with 101 to 299 beds ( P = .03) or hospitals with 100 or fewer beds ( P = .04). Access to care was not associated with patient care financial assistance ( P = .81) or community health programs expenditures ( P = .94). Conclusions: The study hospitals direct most of their community benefit expenditures to patient care financial assistance (individual welfare) rather than population health improvement initiatives, with virtually no investments in community-building activities that address socioeconomic determinants of health.